Counseling on Making Economical Dishwashing Soap to Educate the Rimba Sekampung Community - Nurul Hidayah; Nora Julianti; Muhammad Hafiz Tanjung; Jhon Bona Saragih; Anisya Larasaty; Yoga Hafiz Irawan; Isnaini Putri; Asrifah Lubis; Antoni, Gena Naila; Inez Putri Nabila; Leli Deswita (Indonesian Journal of Advanced Social Works, 2023)
Community Service Program (CSP) is an activity that must be carried out by all students at the University of Riau as a form of dedication and implementation of the knowledge gained during lectures to the community. Students will determine the work programs to be carried out during the KKN activities, one of which is the Socialization of Dishwashing Soap Making. Soap is a product of the chemical industry that is needed by the people of Indonesia. Soap has many variants and can be obtained easily in the market, such as bath soap, washing soap for clothes and household utensils, to soap used in industry. The counseling program for making dishwashing soap was held in Rimba Sekampung Village, Dumai Kota District, Dumai City, Riau Province which was carried out using demonstration methods and direct practice with the community, especially PKK women. The purpose of holding this socialization is to provide MSME business ideas to the community and can also save monthly expenses from PKK mothers. The results of this activity were understanding and inspiration on how to make dish soap and providing business ideas with enormous opportunities, considering that in the Rimba Sekampung area there are many businesses or UMKM engaged in the food sector.